2016
DOI: 10.1590/1679-78252541
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for Severity Estimation of Transversal Cracks in Multi-layered Beams

Abstract: Nowadays, the damage severity evaluation in mechanical structures is mostly performed by analyzing the natural frequency shift. The non-isotropic materials, as the multi-layered ones, are widespread in industrial applications, due to their interesting physicmechanical properties. Thus, a deeper approach of multi-layered beams becomes an important request in the research domain. This paper introduces a damage severity estimator by expressing the crack evolution as a function of stored energy. It is well known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…From paper [15], the beam's free end deflection for the healthy and damaged state is expressed by the mathematical relations:…”
Section: The Finite Element Model Of the Test Structurementioning
confidence: 99%
See 1 more Smart Citation
“…From paper [15], the beam's free end deflection for the healthy and damaged state is expressed by the mathematical relations:…”
Section: The Finite Element Model Of the Test Structurementioning
confidence: 99%
“…In previous studies [15][16][17][18], the authors developed a robust method for detecting, locating and evaluating transverse cracks in all types of beams, regardless of the constraining method, based on the natural frequency changes.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research we approached this topic and found a relation to express the frequency of cracked beams in respect to the damage severity [9] - [11]. The severity is found involving Castigliano's second theorem [12], and it was shown that the severity does not directly depend on the moment of inertia of the damaged cross-section [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this point, it is worth-mentioning that previous works has introduced damage estimators as a function of the strain energy. For instance, Gillich et al expressed the damage severity produced by cracks located in a cantilever, multi-layered beam as a function of the stored energy, in order to study the influence of the crack depth on the natural frequency ship at several longitudinal positions of the beam (Gillich et al 2016). Accurate results were obtained in that work for some vibration modes when compared to experiments.…”
Section: Introductionmentioning
confidence: 99%